2012
DOI: 10.1097/ncq.0b013e31825ba89e
|View full text |Cite
|
Sign up to set email alerts
|

Culture Influence and Predictors for Behavioral Involvement in Patient Safety Among Hospital Nurses in Taiwan

Abstract: This study explored the effects of incident reporting culture and willingness of incident reporting on behavioral involvement in patient safety (BIPS) by surveying 1049 hospital nurses in Taiwan. The highest areas of BIPS were handoff communication and discussion on error prevention. Yet, sharing information about human factors toward safety awareness was less frequent. Results indicated that the reporting culture, willingness to report, tenure of work, and reporting rate contributed positively to BIPS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…This is consistent with other studies. An agreeable safety culture could encourage nurses to engage in safety surveillance, prevention of safety risk, team collaboration and error management (Chiang et al, ; Vogus & Sutcliffe, ). In addition, the study findings illustrated that the nursing safety practices were supportive to their VIR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is consistent with other studies. An agreeable safety culture could encourage nurses to engage in safety surveillance, prevention of safety risk, team collaboration and error management (Chiang et al, ; Vogus & Sutcliffe, ). In addition, the study findings illustrated that the nursing safety practices were supportive to their VIR.…”
Section: Discussionmentioning
confidence: 99%
“…The reporting culture is characterized by non‐punitive learning, system‐driven error management and effective feedback and quality improvement from the reporting, which has been broadly used to measure the organizational culture of patient safety (Kohn et al, ; Sammer et al, ). Researchers found that the reporting culture positively contributed to generic safety acts among nurses (Chiang, Lin, Hsiao, & Chang, ; Vogus & Sutcliffe, ). Similarly, a positive reporting culture can shape and enhance nurses’ safety‐related practices and reporting behaviours.…”
Section: Introductionmentioning
confidence: 99%
“…A reporting culture, summarized from the studies 27 , 28 by Chiang et al, 29 is a combination of the “shared values, attitudes, and behavioral patterns that determine the observable degree of efforts with which all healthcare workers direct their attentions and actions toward incident management and safety assurance at workplace.” 29 The reporting culture and patient safety culture are closely connected. On the one hand, a reporting culture facilitates organization members’ communication and action on patient safety.…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, a reporting culture facilitates organization members’ communication and action on patient safety. 29 32 On the other hand, a healthy patient safety culture helps increase incident reporting. 33 Thus, the high reporting rate in HKUSZH might be consistent with an acceptable patient safety culture in the hospital, which is, in turn, consistent with positive perceptions of overall patient safety culture.…”
Section: Discussionmentioning
confidence: 99%